1999
DOI: 10.1021/jp984080t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Solvation of Coumarin 153 in a Mixture of an Alkane and an Alcohol

Abstract: Molecular dynamics simulations are applied to the preferential solvation of coumarin 153 (C153) by alcohol in an alcohol/alkane mixture, indicated by recent steady-state and time-resolved spectroscopic measurements. Simulations of weakly polar mixtures are done for the ground and the excited states of C153, using detailed models of the dye. Solvation of C153 by the alcohol is almost negligible in the ground state, with correspondingly little effect on the absorption spectrum of the dye, whereas preferential so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 32 publications
7
83
1
Order By: Relevance
“…Interestingly, the most important relative and absolute changes in partial charges have been found by Ladanyi and coworkers [5] on two carbon atoms of C153 (positions 3 and 8). A similar result, related to the same C153 carbon and oxygen atoms, has been obtained by Rempel and coworkers [43] who have performed semiempirical calculations of the charge distributions at the C153 ground and excited states. Additionally, on the basis of their molecular dynamics (MD) simulation of the solvation of C153 in pure MeOH, these authors concluded that the hydrogen bond formed through the oxygen atom at position 12 did not significantly change its energy after C153 excitation.…”
Section: Article In Presssupporting
confidence: 83%
“…Interestingly, the most important relative and absolute changes in partial charges have been found by Ladanyi and coworkers [5] on two carbon atoms of C153 (positions 3 and 8). A similar result, related to the same C153 carbon and oxygen atoms, has been obtained by Rempel and coworkers [43] who have performed semiempirical calculations of the charge distributions at the C153 ground and excited states. Additionally, on the basis of their molecular dynamics (MD) simulation of the solvation of C153 in pure MeOH, these authors concluded that the hydrogen bond formed through the oxygen atom at position 12 did not significantly change its energy after C153 excitation.…”
Section: Article In Presssupporting
confidence: 83%
“…Other examples of nonlinear solvation dynamics have appeared in studies of solvent mixtures. 7 In mixtures, the ground state of the solute is preferentially solvated by one component of the mixture, while the excited state may be preferentially solvated by the other component. This means that significant rearrangement of the first solvent shell is required to relax the excited state, requiring solvent motions that are not present at equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 compares the equilibrium solvent response function C(t) (solid curves; same as in Figure 6 of our previous paper 20 ) to the nonequilibrium solvent response S(t) (dotted curves) for two realistic cases: that of a neutral solute that is ionized, resulting in a 20% size decrease (upper panel), and that of a neutral solute that gains an electron, resulting in a 20% size increase (center panel). The lower panel shows the equilibrium (solid curve) and nonequilibrium (dotted curve) solvent response functions for the case explored by most previous simulation studies: [5][6][7][8][9][10][11][13][14][15] that of a change in solute charge without an accompanying change in size. For this latter case, other than slightly overestimating the magnitude of the inertial component, LR does an excellent job of predicting the nonequilibrium solvent response (Table 1), in agreement with the previous work of Maroncelli and Fleming.…”
Section: Breakdown Of Linear Response For Nonpolar Solvationmentioning
confidence: 99%
“…That is why this phenomenon is also called ''the dielectric enrichment''. Computer simulations at the molecular level present the most widely applied approach for modeling numerically such systems in the recent time [1][2][3][4][5][6][7][8]. The references cited here are most close to the theme of the present work; a more comprehensive reference list can be extracted from these references.…”
Section: Introductionmentioning
confidence: 98%